Physiological and biochemical changes in leaves of radish (Raphanus sativus L. cherry bella) seedlings treated with sodium nitroprusside (SNP) - Çanakci-Gülengül, Songül; Karabulut, Fadime (Pakistan Botanical Society, 2018)
In the present study, SNP (0, 50, 100, 200, and 300 ?M) was administered hydroponically to 10 –day-old seedlings of radish (Raphanus sativus L. cherry bella) through roots for 5 days and physiological and biochemical effects on leaves were examined. It was determined that compared to control; leaves had loss of pigment (chl a+b and carotenoid), soluble protein content was declined and MDA and GSSG contents were increased. In addition, GSH content and SOD activity was decreased whereas CAT activity was increased. While % rates of fatty acids in the leaf were declined and exceptionally decreased for palmitic, linoleic and palmitoleic acid, it showed an increase and an exceptional increase for stearic and linolenic acid. Generally, high doses of SNP significantly triggered the toxicity. © 2018, Pakistan Botanical Society. All rights reserved.
Keywords: Raphanus sativus L; Sodium nitroprusside; Toxic stress